CT Measurement of Maxillary Sinus Volume Among the Population of Rajshahi District in Bangladesh - Afrin, Sadia; Rabbi, DHM Fazle; Mustafa, Rashed; Ahmed, Wali; Afroze, Akhtari (TAJ: Journal of Teachers Association, 2023)
Background: The volumetric measurement of the maxillary sinuses is essential in assessing the incidence of sinusitis and cancer and measuring the intimate relationship between teeth and maxillary sinuses. There have been reports in multiple studies that there is racial variation concerning age and gender. This study aims to determine whether the sinus volume of males and females differ and its relation to age. Methods: This descriptive observational study was carried out among 100 respondents between the age of 11- 60 years who were residing in Rajshahi during the study period of one year, i.e., January 2018 to December 2018. The data has been collected from the Department of Radiology and Imaging of Rajshahi Medical College Hospital (RMCH) from the patients who had undergone CT scan examinations. The measurements were directly taken from a computer provided with an electronic caliper. After that, the sinus volume was calculated manually using the following formula (height x width x depth x 0.5). The quality of the data was obtained diligently, and ethical issues were properly maintained in all the steps of this study. Results: There were 50 males and 50 females, ranging from 11 – 60 years of age, where the mean (± SD) age was 36.7 (± 14.8) years. The mean (± SD) volume of the maxillary sinus in the male group was 17 (± 4.6) cm3 for the right side and 17.5 (± 4.7) cm3 for the left side, which was significantly more than the female group, 14.7 (± 3.7) cm3 for the right side and 15.1 (± 3.7) cm3 for the left side (p = 0.031). Concerning age, the distribution of maxillary sinus volume showed the highest values between 21-30 years of age, and then it decreased both on the right and left side; this finding was found to be statistically significant (p = 0 .018). Conclusion: This study provides salient information regarding maxillary sinus volume among the people of the Rajshahi district of Bangladesh. This study's results will help establish a reference dataset regarding anatomical measurements of the maxillary sinus. TAJ 2022; 36: No-1: 83-87